Simultaneous HPLC Determination of Five Active Ingredients in Belladonna tincture - Gao, Jie; Cheng, Weiming; Huang, Wei; Yue, Chao; Shi, Bei; Zhang, Wenting (Asian Journal of Chemistry, 2014)
An HPLC method is established for the simultaneous determination of five active ingredients (scopolin, chlorogenic acid, kaempferol-3-O-b-D (6-O-a-L-rhamnogalactoside)-7-O-b-D-glucoside, scopoletin and rutin). HPLC conditions included Agilent Kromesil 100-5 C18 column (4.6 mm × 250 mm, 5 μm) and the mobile phase was a mixture of methanol and 0.05 % phosphoric acid for gradient elution. The flow rate was 1 mL/min. The column temperature was at 30 ºC. Five active ingredients had good linear relationships: Scopolin in the range of 0.0326-0.978 μg (R2 = 0.9999), chlorogenic acid in the range of 0.0100-0.300 μg (R2 = 0.9996), kaempferol-3-O-b-D (6-O-a-L-rhamnogalactoside)-7-O-b-D-glucoside of 0.0319-0.957 μg (R2 = 0.9996), scopoletin in the range of 0.0363-1.089 μg (R2 = 0.9995) and rutin in the range of 0.0101-0.303 μg (R2 = 0.9994). Their average recoveries were 99.59 % (RSD = 1.9 %), 96.92 % (RSD = 1.9 %), 96.41 % (RSD = 1.5 %), 96.46 % (RSD = 2.2 %) and 97.45 % (RSD = 1.9 %), respectively. This method was steady with high precision and good repeatability. It could be used for the determination of the five active ingredients and quality control of Belladonna tincture.